مســـرحة الشــــعر في ديوان:" طاسيليا" لـعــز الدين ميهوبي - عبد القادر لباشي (Université de M'sila, 2019)
ملخص: تتوخى هذه القراءة النبش في طبقات الكتابة بمساحتها الواسعة وفضائها اللامتناهي، الضّاج بأجناس عدّة، تداخلت بلا موعد، واستحالت لونا واحدا، وصار احتفاظ كل من هذه الأجناس بحدوده أمرا صعبا وشائكا. أو هكذا كما قرر (ياكبسون): لقد صارت الحدود بين الشعر والنثر أقل استقرارا من الحدود الإدارية للصين. وقد حظي الشعر كما المسرح عبر تاريخهما الطويل بمكانة خاصة، ألم يسيرا إلى مجرى واحد، ألم يكن المسرح في بدايته شعرا ؟ ألا يذكر لنا التاريخ الأدبي والفني في المسرح الإغريقي شعراء كبار: اسخيلوس، سوفوكليس، ويوروبيدس. أمّا في الشعر العربي المعاصر فقد حدث الاقتراب من جماهير الشعر عن طريق آلية (المسْرحة)، إذْ الهدف من هذه النصوص هو جعلها قابلة للتمثيل والعرض بالدرجة الأولى. وفي شعرنا الجزائري المعاصر يبرز ديوان: ( طاسيليا ) للشاعر عز الدين ميهوبي أنموذجا واضحا لمسرحة الشعر، عن طريق (أنسنة) الشخصيات، ضمن حوارات مكثفة، وفي حضور لأصوات متعددة، واشتغال على الفضاء الكتابي، واستثمار لقنوات التبليغ المختلفة. الكلمات المفتاحية: المسرحة – الشعر- طاسيليا Abstract: This reading is intended to examine the stratification of the writing layers with their wide and endless space, which is full of different kinds, overlapping with no date and one color, and each of these races maintaining their boundaries is difficult and difficult. Or so, as Jacobson decided: the border between poetry and prose has become less stable than China's administrative borders. Poetry, like the theater through their long history, had a special place, weren’t they a single one. Wasn’t the theater at the beginning poetry? Doesn’t the literary and artistic history of the Greek theater remind us of the great poets: Asechylus, Sophocles, and Europides? In modern Arabic poetry, they have come close to the masses of poetry through the mechanism of drama. In our contemporary Algerian poetry, (Tassilia) presents to the poet Azzedine Mihoubi a clear example of the drama of poetry through the humanization of personalities in intensive dialogues, in the presence of multiple voices, working on the written space and investing in different channels of reporting. Keywords: Theatrical - Poetry - Tassilia
Keywords: المسرحة – الشعر- طاسيليا